Organoleptic scoring of RTS prepared from bael (Aegle marmelos) varieties - SINGH, A K; SINGH, SANJAY; SINGH, R S; MAKWANA, PURNIMA (The Indian Journal of Agricultural Sciences, 2016)
Bael (Aegle marmelos correa) can be cultivated in varied agro-climatic conditions of the most parts of India. The wastelands of country can easily be made productive by growing such a hardy tree having high nutritional and therapeutic significance. It is a rich source of vitamin B (riboflavin) and have long storage life. To make best use of fruits particularly which can not be consumed directly as table fruit, but can easily be commercialized by popularizing the value added products which are rich in nutraceutical and medicinal value. Among the varieties, there was great difference in their physico-chemical and organoleptic rating for RTS. The present study was conducted to find out the best RTS prepared from pulp of different bael varieties which can be stored and used for the further application. Among the varieties, the fruits of Goma Yashi had all the desirable qualitative characters, i.e. appropriate size, pulp colour, fruit shape, less seed, less fibre, less acidity and thin shell. In all the varieties, the highest organoleptic rating score in terms of acceptability (8.40), appearance (7.94), taste (8.15) and colour (8.41) was observed in Goma Yashi followed by NB 5, Thar Divya and CISHB 1 from the prepared RTS. These factors play a significant role in preparation of quality RTS. Amongst the varieties, Goma Yashi, NB 5, Thar Divya and CISHB-1 had high qualitative characters and found to be suitable for RTS preparation. These varieties can be commercialized by popularizing value added product RTS.